Nitrogen effect on growth and carrageenan content in Gigartina canaliculata Harv. (Rhodophyta, Gigartinales), in outdoor tank cultures - MA González-Gómez; JA Zertuche-González; I Pacheco-Ruíz (Ciencias Marinas, 1992)
Gigartina canaliculata was cultivated under different nutrient conditions in 100-l tanks, to study the effect on growth and yield and quality of carrageenan. The cultures were under four frequencies of pulse fertilization: every 2, 4, 7 and 14 days, for seven weeks. The doses for each fertilization consisted of 100:00 µM of NO3–:PO4–2 for three hours. An inverse relationship was observed between growth and carrageenan yield: the highest growth was observed in the more fertilized culture (5.5% day–2), whereas the highest carrageenan yield was observed in the less fertilized culture (49%). Maximum gel strengh was 41 g cm–2 for the more fertilized cultures (two and three times a week). However, there were no significant differences in the sulfate content among the treatments (22%). The different nutrient doses resulted in a difference in carrageen a yield of approximately 5% among the highest and the lowest fertilized culture. The production of biomass, however, was 1.8 times higher for the more fertilized culture. Thus, carrageenan yield production per tank was much higher for the more fertilized culture.